DAMPAK ONLINE GAME TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS XI DI SMA NEGERI 2 SIDUA’ORI - Reforman Jaya Hulu (Counseling For All : Jurnal Bimbingan dan Konseling, 2024)
The problem in this research is the impact of online games on the students’ learning achievement, especially in Mathematics subject. The purposes of this research are (1) to describe the impact of online games on students’ learning achievement, dan (2) to describe the students’ achievement at the eleventh grade of SMA Negeri 2 Sidua’ori. The type of this research is qualitative research and descriptive approach. Then, data in this research is the impact of online game on students’ learning achievement. The data source in this research obtained from the results of interview and obtained from school’s documentations. The techniques of data collection in this research are observation, interview and documentation techniques. Furthermore, the data analysis technique is used in this research are data reduction, data display and drawing conclussion. The results of this research show that (1) Online games have the negative impacts on the students’ learning achievement, which the students are so addicted to online games that they ignore learning activities and homework given by the teacher. (2) the students’ learning achievement especially in Mathematicts subject still low, which they obtain the average value is below the KKM (Minimum Completion Criteria). Therefore, the researcher gives some suggestions namely the results of this research should be an evaluation in giving education related the impact of online games on students’ learning achievement through counseling guidance so the students have motivation or enthusiastic learning in joining the learning process in the school.